Empirical analysis on the relationship between good import, good export, Tariff and economic growth - CHAN, Ting Fung (2019)
Abstract In this research, the objective is studying the relationship between tariff, good import, good export, and economic growth to understand the possible influences of Trump Tariff imposed since 2017. The relationship between tariff with economic growth and good import, good export with economic growth remain ambiguous. This research combined both to study their relationships. The methods of cointegration test and OLS regression are conducted to study the long term and short term relationship with panel data analysis from 2000 to 2017 from 132 countries. The result shows that there is no significant relationship from the tariff, good import, and good export to economic growth. Result suggests that Trump Tariff has insignificant influences to improve trade deficits and furthermore, economic growth.